2015
DOI: 10.3171/2014.11.jns141109
|View full text |Cite
|
Sign up to set email alerts
|

Comparisons between small intestinal and gastric feeding in severe traumatic brain injury: a systematic review and meta-analysis of randomized controlled trials

Abstract: Severe traumatic brain injury (TBI) is a catastrophic event that often has destructive familial, economic, and societal consequences. It contributes to many deaths and cases of permanent disability, especially among patients 15-30 years old. 8,10 The average mortality rate for patients with severe TBI is 39%, and 60% of these patients have an unfavorable outcome on the Glasgow Outcome Scale. 24,26 Furthermore, those who survive tend to have significant disabilities, which also can cause a major socioeconomic b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 29 publications
0
9
0
1
Order By: Relevance
“…Their study demonstrated that postpyloric EN reduces the incidence of VAP and decreases the incidence of gastric residuals. Additionally, a meta-analysis involving five randomized controlled studies revealed that severe TBI patients who were administered postpyloric EN exhibited a reduced incidence of VAP (RR 0.52, 95% CI 0.34–0.81; P = 0.003; I 2 = 0.0%) and fewer total complications compared with patients who were administered gastric EN [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Their study demonstrated that postpyloric EN reduces the incidence of VAP and decreases the incidence of gastric residuals. Additionally, a meta-analysis involving five randomized controlled studies revealed that severe TBI patients who were administered postpyloric EN exhibited a reduced incidence of VAP (RR 0.52, 95% CI 0.34–0.81; P = 0.003; I 2 = 0.0%) and fewer total complications compared with patients who were administered gastric EN [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of severe pneumonia was significantly higher in the PEG group. This result was expected and clinically plausible because enteral nutrition administered via PEG poses a risk of gastroesophageal reflux and aspiration pneumonia owing to the underlying pharyngeal and laryngeal dysfunction of patients who require feeding through this modality [23,35,47]. Switching from PEG feeding to TPN may be an option for patients who underwent PEG feeding and repeatedly suffered from aspiration pneumonia because TPN is more effective in reducing the risk of severe pneumonia than PEG feeding.…”
Section: Discussionmentioning
confidence: 99%
“…A study of 74 critically ill children randomly assigned to gastric or post-pyloric feeds demonstrated no difference in complications, and patients receiving post-pyloric feeds received more of their prescribed calories ( 120 ). A large meta-analysis of adult patients with severe traumatic brain injury demonstrated a decreased risk of pneumonitis with post-pyloric feeds ( 121 ). Other researchers found an increased risk of gastrointestinal complications when post-pyloric feeds were used in septic patients or patients on epinephrine (Table 1 ) ( 37 , 122 ).…”
Section: Route Of Nutritionmentioning
confidence: 99%
“…Despite the results of the PEPaNIC study, equipoise remains in the pARDS population. The optimal macronutrient dose, timing, and formulation of EN and PN support has yet to be elucidated as increasing evidence demonstrates links between the immune system, homeostasis, and nutritional intake ( 121 , 126 129 ).…”
Section: Route Of Nutritionmentioning
confidence: 99%